PERGESERAN PARADIGMA PADA LAYANAN PERIJINAN MELALUI NEW MODEL SERVICE BERBASIS CITIZEN CENTRIC - Dwi Suharnoko; Umi Chayatin; Chandra Dinata (Journal of Public Administration and Local Governance, 2018)
An important point in good governance is essentially the provision of excellent service to people who have citizenship rights that must be provided by the government. Globalization has encouraged paradigm changes in government in carrying out its distributive function to the community. As much as developed countries have done, public encouragement accompanied by public participation in all governance processes leads the country to "virtual" spaces with sufficient coverage to facilitate its citizens to participate in all national and state affairs, the autonomy space given to the region is able to make local governments self-reliant, innovative, and creative in providing services to the community. The research conducted in Integrated Licensing Service Agency of Malang Regency shows that the satisfaction of the society is good enough to the service product given, if it is categorized the assessment from public perception of the service given is A (very good). To achieve that, of course, the integrated licensing agency of Malang regency through a long way to reach it starting from building a mutual commitment to change the more autonomous institution in carrying out the service function to the society.